Answer :

To prove:


Let, y =


let, x = cos 2θ


θ = 1/2 cos-1 x …(1)


we know that-


1 + cos 2θ = 2cos2θ


And 1 – cos 2θ = 2sin2θ


y =


y =


y =


y =


y =


y =


We know that: tan(x - y) =


y =


y = {from 1}


From basic ITF formula we know that –


tan-1(tan x) = x if x (-π/2 , π/2)


Given,


(-1/√2) ≤ x ≤ 1


0 ≤ cos-1x ≤ 3π/4


-3π/8 ≤ -(1/2)cos‑1x ≤ 0


-π/8 < π/4 – (1/2)cos-1x ≤ π/4


Thus,



y = ,


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers